2020
DOI: 10.1080/13540602.2020.1740195
|View full text |Cite
|
Sign up to set email alerts
|

Perceived classroom goal structures as predictors of students’ personal goals

Abstract: This study focused on the question of how to enhance a mastery-goal orientation in the classroom. We started from the perspective of the achievement goal theory, which assumes that the goals that students have (personal goals) relate to the goals that are set in the classroom (classroom goal structures). In classrooms where teachers focus on learning and effort-instead of normative standards and social comparison-mastery goals are enhanced. This type of classroom can be endorsed by focusing on the following cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Goals orientation is a dynamic concept [35]. The success and failure in previous task accomplishment [10,35,36], as well as the experienced situation in the classrooms [37,38], are used to redefine future goal orientations and intention. The old students have generally experienced the success and failure in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Goals orientation is a dynamic concept [35]. The success and failure in previous task accomplishment [10,35,36], as well as the experienced situation in the classrooms [37,38], are used to redefine future goal orientations and intention. The old students have generally experienced the success and failure in their study.…”
Section: Discussionmentioning
confidence: 99%
“…In a longitudinal study conducted with faculty members, Daumiller et al (2023) found out that achievement goals are effective on faculty members’ burnout levels and performance. Fokkens-Bruinsma et al (2018) revealed that there is a significant relationship between teachers’ motivation for their work and their students’ achievement goals.…”
Section: Discussionmentioning
confidence: 99%
“…Motivated learners exhibit higher performance and life-satisfaction levels and show higher levels of perseverance (OECD, 2017). Several studies have investigated what teachers should do (Ahn et al, 2021;Dalehefte & Canrinus, 2023;Domen et al, 2020) and how classrooms should be organized (Fokkens-Bruinsma et al, 2020;Jong, 2020) to optimize learners' motivation (Bec´irovic´et al, 2022;Owen & Thomas, 2021). Adaptive teaching and differentiated instruction have been shown to play a role in motivating pupils (Guay et al, 2017;Sapan & Mede, 2022).…”
Section: Introductionmentioning
confidence: 99%